Patterns and factors associated with pneumococcal vaccination in a prospective cohort of 1,697 patients with rheumatoid arthritis - Thomas, Konstantinos; Lazarini, Argyro; Kaltsonoudis, Evripidis; Voulgari, Paraskevi V.; Drosos, Alexandros A.; Repa, Argyro; Sali, Ainour Molla Ismail; Sidiropoulos, Prodromos; Tsatsani, Panagiota; Gazi, Sousana; Fragkiadaki, Kalliopi; Tektonidou, Maria G.; et al. (Frontiers in Medicine, 2023)
Introduction: Patients with rheumatoid arthritis (RA) are at increased risk for serious infections. Pneumococcal vaccination is among the most important preventive measures, however vaccine uptake is suboptimal. We explored the rate and factors associated with pneumococcal vaccination in a contemporary RA cohort. Materials and methods: Multi-center, prospective, RA cohort study in Greece. Patient and disease characteristics and influenza and pneumococcal vaccinations were documented at baseline and three years later. Results: 1,697 patients were included and 34.5% had already received at least one pneumococcal vaccine at baseline. Among 1,111 non-vaccinated patients, 40.1% received pneumococcal vaccination during follow-up, increasing the vaccine coverage to 60.8%. By multivariate analysis, positive predictors for pneumococcal vaccination included prescription of influenza vaccine (OR=33.35, 95%CI: 18.58-59.85), history of cancer (OR=2.35, 95%CI: 1.09-5.06), bDMARD use (OR=1.85, 95%CI: 1.29-2.65), seropositivity (OR=1.47, 95%CI: 1.05-2.05) and high disease activity (DAS28-ESR, OR=1.33, 95%CI: 1.17-1.51). Male sex (OR=0.65, 95%CI: 0.43-0.99) was a negative predictor for pneumococcal vaccination during follow-up. Discussion: Despite increasing rates of pneumococcal vaccine coverage, 40% of RA patients remain unvaccinated. Severe disease, biologics use, comorbidities and more importantly flu vaccination were the most significant factors associated with pneumococcal vaccination, emphasizing the currently unmet need for cultivating a “vaccination culture” in RA patients.